Investigation on remelting solution heat treatment for nickel-based single crystal superalloys. (15th July 2017) - Zhang, Yanbin; Liu, Lin; Huang, Taiwen; Li, Yafeng; Jie, Ziqi; Zhang, Jun; Yang, Wenchao; Fu, Hengzhi
Abstract: To increase the peak temperature during solution heat treatment of a single crystal superalloy over the solidus, a remelting solution heat treatment is investigated. It contains two parts: a) homogenizing at mushy zone temperatures, and ignoring partial incipient melting; b) eliminating incipient melting structure by secondary solution heat treatment. After remelting solution heat treatment the refining γ′ particles uniformly distributed and the residual segregations are less than those after traditional solution heat treatment. Therefore, the rupture life at 1100 °C/150 MPa is improved from 105.3 h after traditional solution heat treatment to 141.1 h. Graphical abstract: